The effect of compaction method on the compressive strength and porosity of normal concrete - Yose Fajar Pratama; Eka Juliafad (Universitas Negeri Padang, 2026)
This study investigates how community-like compaction practices affect density, porosity, and compressive strength of normal concrete across different workability levels. A factorial laboratory experiment (4 compaction methods × 3 slump targets) was conducted using 150×300 mm cylinders (n=72; six replicates per group). Concrete was proportioned to SNI 03-2834-2000; control compaction followed SNI 2493:2011; 28-day strength was tested per SNI 1974:2011; porosity was measured using an ASTM C642-based procedure. Slump was set at 5, 7, and 11 cm by varying water content. Fresh mass decreased as compaction became less effective, indicating lower achieved density and greater entrapped air: compared with SK, hammer vibration (SH) and no compaction (SP) were 7–9% lighter. Porosity increased markedly under inadequate compaction, with SP reaching 22.36–26.81% versus 10.16–14.22% for SK. Compressive strength followed the same ordering: SK achieved 18.99–22.94 MPa, while SH and SP dropped to 9.90–13.93 MPa and 8.49–13.35 MPa, respectively, with losses up to 58% relative to SK depending on slump. Overall, slump alone did not guarantee performance when compaction was poor. Rodding (SR) provided intermediate results, maintaining mass close to SK and limiting strength loss compared with SH/SP. An inverse porosity–strength relationship was observed across slumps.